Analisis Proses Pengelasan Pada Bonnet d Departemen Welding Shop Untuk Mengurangi Resiko Kerusakan Pada Proses Pengelasan: Welding Process Analysis At Bonnet d Welding Shop Department To Reduce The Risk Of Damage To The Welding Process - Refdilzon Yasra; Dasman Johan; Muhammad Fajri Hafiizh (Engineering and Technology International Journal, 2022)
The method that will be used in this research is the Continuous improvement method. Process improvement using the Continuous improvement method can prevent abnormal welding processes, and it is carried out continuously so that it can improve work processes and achieve good employee productivity. The Work Sampling method is used to conduct a large number of observations on the work activities of machines, processes, workers or operators at the Welding Shop Department of PT. Cameron Systems Batam. Based on the research, the standard time of the current Bonnet welding process is 1167.5 minutes or equal to 19 hours 45 minutes for 1 unit of Bonnet welding. The focus of method improvement carried out on fishbone analysis, including Man (Operator), Method (Method), Material, Machine, (Machine), Measurements, Milieu (Environment) factors. It is an improvement priority that must be applied to the welding shop department in increasing the productivity of current employees.